Intensity modulation using chirped fiber bragg grating as an edge filter for temperature sensing. Issue 12 (December 2014) - Srivastava, Deepa; Bhatnagar, Randhir; Kumar, Asha; Parmar, Vinod
ABSTRACT We demonstrate a prominent technique using intensity variation owing to a change in temperature of fiber Bragg grating (FBG) instead of just a shift of Bragg wavelength due to ambient temperature variation. The rising and falling region of chirped fiber Bragg grating (CFBG) spectrum can be used as edge filter, where intensity variation can be observed with the shift in wavelength due to change in temperature. The proposed hypothesis of intensity variation with a shift in wavelength at rising edge of CFBG has been investigated theoretically and later on these results are verified experimentally. The rising and falling edge of CFBG are analyzed and then FBG was written on 1542.4 nm. The rising edge of CFBG have linear region in the range of 1542.3–1542.7 nm wavelength. Thus intensity will be modulated linearly with a shift of Bragg wavelength in this region. In‐house fabricated FBG has been used and CFBG as an edge filter was implemented in our experiment to verify the proposed concept of intensity modulation. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2913–2915, 2014